Coronary computed tomographic angiography derived findings and risk score improves the allocation of lipid lowering therapy compared to clinical score. Issue 6 (11th February 2022) - Jaltotage, Biyanka; Gupta, Ashu; Ali, Umar; Huangfu, Gavin; Rankin, Jamie; Parsons, Richard; Dwivedi, Girish
Abstract : Abstract: The initiation of therapy for atherosclerotic cardiovascular disease (ASVCD) is currently guided by cohort-based risk scores. Coronary computed tomographic angiography (CCTA) offers more personalised risk assessments to optimise therapy allocation. This study investigates the utility of CCTA determined coronary stenosis (both obstructive and non-obstructive plaque) to guide allocation of lipid lowering therapy. A retrospective analysis of 450 patients with CCTA performed for the assessment of chest pain at a single centre was conducted. Baseline characteristics, investigations, treatments and clinical outcomes were recorded. The allocation of lipid lowering therapy was evaluated with three models, cohort-based risk score (pooled cohort equation), a previously validated CCTA based clinical risk score (pooled cohort equation and CCTA findings) and CCTA alone (without clinical characteristics). The reclassification analysis included 266 patients. Compared to the cohort-based risk score, CCTA based clinical risk score in total reassigned 23% of patients. CCTA alone compared to the CCTA based clinical risk score correctly reassigned 23% and incorrectly reassigned 10%. When comparing the performance of CCTA alone against the cohort-based risk score, both the additive NRI of 25.8 (95% CI 4.12–37.56) and absolute NRI of 13.2 (95% CI 5.88–19.77) was significant. Revascularisation was required in 3% with a low cohort-based risk, but no patients with low risk as per CCTA alone or CCTA based clinical risk score required revascularisation The use of a CCTA based clinical risk score or CCTA alone compared to cohort-based risk scores can improve the allocation of lipid lowering therapy.